1266 Occupational safety and concussion injury awareness of irish professional and semi-professional footballers. (24th April 2018) - Buggy, CJ; Coffey, N; Lawless, M; Kelly, S
Abstract : Introduction: The purpose of the study was to investigate the occupational safety awareness of a cohort of professional athletes; specifically looking at the risk of concussion, reporting rates, and practices amongst professional and semi-professional footballers. Methods: The study was an empirical quantitative study, in the form of a census, of a particular cohort (n=250) conducted in 2015. Participants were professional or semi-professional footballers playing in the League of Ireland. Footballers undertook a questionnaire on safety awareness and self-reported concussion over the previous five playing seasons. 149 footballers participated (60% response rate, >90% CI). Data was analysed using SPSS. Results: Over two thirds of respondents were unaware if their football club had a formal safety programme. Results indicated footballers had little occupational safety awareness, though they felt that both management and teammates employed good safety practices. 32% of respondents stated they had sustained a concussion between 2010%–2013. 84% of respondents noted they had not sustained a concussion during 2014. However, there were a significant number of semi-professional defenders who sustained a concussion that year. There was a higher rate of self-reported concussion amongst League of Ireland footballers in 2014 than in a similar study carried out on professional footballers in Italy in 2009. Respondents were more likely to report a concussion to a physiotherapist or doctor. Respondents were asked to identify a reason for not reporting a concussion, the most prominent being that players lacked unawareness of concussion impacts. Conclusion: Concussion reporting by mainstream media coupled with an introduction of concussion awareness programmes has resulted in a general increase in personal safety knowledge and awareness of concussion amongst Irish footballers. Further studies are needed focussing on safety culture and occupational safety and health awareness is raised in the professional sporting sector.